Does the Perception of Happiness Change with Age? - Şehribanoğlu, Sanem (Fırat University, 2025)
The measurement of societal happiness is of paramount importance in the development of effective social policies by governments and institutions, as well as in the evaluation of the efficacy of such policies. This study sought answers to the question of whether the factors that make individuals happy change at different ages. For this purpose, the 2019 data of the Life Satisfaction Survey implemented by the Turkish Statistical Institute (TurkStat) were used. The study categorised happiness as either 'happy' or 'unhappy' and 162 variables were selected for analysis. To enhance the study's efficiency and reduce the number of variables, the correlation-based feature selection algorithm, a machine learning algorithm, was employed. The study concluded that age exerts a significant influence on happiness, with distinct expectations and perceptions of happiness across age groups. It was determined that factors such as life satisfaction, hope, income, social life, debt, family and relatives were not influenced by age changes. However, the findings revealed that certain variables emerged as predominant in different age groups. In the young, unemployment, job loss, education status, marital status and pressure due to political views were highlighted, while in the middle age group, religious beliefs and comparisons with the past period were emphasised. In the elderly group, variables such as personal care, access to health services, water quality, transportation services and cheap product preference were determined to have a significant effect.

Toplumların mutluluğunu ölçmek, hükümetlerin ve kurumların halkın refahını artıracak politikalar geliştirmesine yardımcı olduğu gibi sosyal politikaların ne kadar etkili olduğunun tespit edilmesi açısından da önemlidir. Bu çalışmada, bireyleri mutlu eden faktörlerin farklı yaşlarda değişim gösterip göstermediği sorusuna yanıtlar aranmıştır. Bu amaç için Türkiye İstatistik Kurumu (TÜİK) tarafından uygulanan Yaşam Memnuniyeti Araştırması’nın 2019 verilerinden yararlanılmıştır. Çalışmada mutluluk değişkeni mutlu ve mutsuz olarak sınıflandırılmış ve 162 değişken analizlerde kullanılmak üzere belirlenmiştir. Çalışmanın verimliliğini artırmak ve değişken sayısını azaltmak amacıyla özellik seçim algoritmalarından biri olan korelasyon tabanlı özellik seçim algoritması kullanılmıştır. Çalışmada yaşın mutluluk üzerinde önemli bir etkiye sahip olduğu, yaş grupları arasında mutlulukla ilgili farklı beklenti ve algıların olduğu sonucuna varılmıştır. Yaşam memnuniyeti, umut, gelir, sosyal yaşam, borç, aile ve akrabalar gibi faktörlerin yaş değişimlerinden etkilenmediği belirlenmiştir. Ancak bulgular, farklı yaş gruplarında belirli değişkenlerin ön plana çıktığını ortaya koymuştur. Gençlerde işsizlik, iş kaybı, eğitim durumu, medeni durum ve siyasi görüşler nedeniyle oluşan baskı, orta yaş grubunda dini inançlar ve geçmişle yapılan karşılaştırmalar ön plana çıkmıştır. Yaşlı bireylerde ise kişisel bakım, sağlık hizmetlerine erişim, su kalitesi, ulaşım hizmetleri ve ucuz ürün tercihi gibi değişkenlerin önemli bir etkisi olduğu belirlenmiştir.
Yaşa Göre Mutluluk Algısı Değişir Mi?
Keywords: Quantitative Methods in Sociology; Sosyolojide Niceliksel Yöntemler; Sociology (Other); Sosyoloji (Diğer); Community Psychology; Topluluk Psikolojisi